Șima İmșir. Health, Literature and Women in Twentieth-Century Turkey: Bodies of Exception. - Nuri, Ahmed (Zemin, 2024)
Kitabiyat: Șima İmșir. Health, Literature and Women in Twentieth-Century Turkey: Bodies of Exception. New York: Routledge, 2023. 212 p., ISBN 9781032009438.